Challenges and controversies in the conservative management of uterine and ovarian cancer. (February 2019) - Janda, M.; McGrath, S.; Obermair, A.
Abstract: Uterine cancer is the fifth most common cancer in women worldwide with an estimated 320, 000 annual diagnoses. Its most common form, endometrioid adenocarcinoma of the endometrium (endometrial adenocarcinoma [EAC]), is thought to develop through excessive proliferation of endometrial glands, and then increasing steadily in incidence. The current standard treatment for EAC is hysterectomy, which is often curative. However, it may be unacceptably expensive for women with severe medical comorbidities, those who are at risk of intra- and postoperative adverse events and those who desire fertility. Ovarian cancer is the most malignant of all gynaecological cancers, but patients with disease limited to one ovary and patients with non-epithelial tumours may expect a good prognosis. A selected group of young patients who desire fertility may be well treated with conservative surgery. This chapter reviews patient selection, diagnosis, pre-treatment evaluation, treatment options, surveillance and risk of relapse. Highlights: Conservative treatment of patients diagnosed with endometrial cancer is experimental and should be limited to clinical trials. Patients who benefit from a nonsurgical approach include elderly patients with multiple medical comorbidities, young women who desire fertility and patients who prefer to avoid surgery. Unresolved problems around non-surgical treatment of endometrial cancer include acceptability by patients, pregnancy and recurrence outcomes. Fertility-sparing surgery for ovarian cancer requires meticulous surgical staging. The role of postoperative chemotherapy is yet to be determined. Pregnancy outcomes after fertility-sparing surgery for ovarian cancer are generally effective.